Combined immunization against TGF-β1 enhances HPV16 E7-specific vaccine-elicited antitumour immunity in mice with grafted TC-1 tumours. (5th November 2018) - Chu, Xiaojie; Li, Yang; Huang, Weiwei; Feng, Xuejun; Sun, Pengyan; Yao, Yufeng; Yang, Xu; Sun, Wenjia; Bai, Hongmei; Liu, Cunbao; Ma, Yanbing
Abstract: Therapeutic vaccine appears to be a potential approach for the treatment of human papillomavirus (HPV)-associated tumours, but its efficacy can be dampened by immunosuppressive factors such as transforming growth factor (TGF)-β1. We sought to investigate whether active immunity against TGF-β1 enhances the anti-tumour immunity elicited by an HPV16 E7-specific vaccine that we developed previously. In this study, virus-like particles of hepatitis B virus core antigen were used as vaccine carriers to deliver either TGF-β1 B cell epitopes or E7 cytotoxic T-lymphocyte epitope. The combination of preventive immunization against TGF-β1 and therapeutic immunization with the E7 vaccine significantly reduced the growth of grafted TC-1 tumours in C57 mice, showing better efficacy than immunization with only one of the vaccines. The improved efficacy of combined immunization is evidenced by elevated IFN- γ and decreased IL-4 and TGF-β1 levels in cultured splenocytes, increased E7-specific IFN- γ -expressing splenocytes, and increased numbers of CD4 + IFN- γ + and CD8 + IFN- γ + cells and decreased numbers of Treg (CD4 + Foxp3 + ) cells in the spleen and tumours. The results strongly indicate that targeting TGF-β1 through active immunization might be a potent approach to enhancing antigen-specific therapeutic vaccine-induced anti-tumour immune efficacy and providing a combined strategy for effective cancer immunotherapy.